Detection of L-Cysteine in wheat flour by Raman microspectroscopy combined chemometrics of HCA and PCA - Cebi, Nur; Dogan, Canan Ekinci; Develioglu, Aysen; Yayla, Mediha Esra Altuntop; Sagdic, Osman (ELSEVIER SCI LTD, 2017)
L-Cysteine is deliberately added to various flour types since L-Cysteine has enabled favorable baking conditions such as low viscosity; increased elasticity and rise during baking. In Turkey, usage of L-Cysteine as a food additive isn't allowed in wheat flour according to the Turkish Food Codex Regulation on food additives. There is an urgent need for effective methods to detect L-Cysteine in wheat flour. In this study, for the first time, a new, rapid, effective, non-destructive and cost-effective method was developed for detection of L-Cysteine in wheat flour using Raman microscopy. Detection of L-Cysteine in wheat flour was accomplished successfully using Raman microscopy combined chemometrics of PCA (Principal Component Analysis) and HCA (Hierarchical Cluster Analysis). In this work, 500-2000 cm(-1) spectral range (fingerprint region) was determined to perform PCA and HCA analysis. L-Cysteine and L-Cystine were determined with detection limit of 0.125% (w/w) in different wheat flour samples. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: L-Cysteine; L-Cystine; Raman microscopy; HCA; PCA; Wheat flour; SPECTROSCOPY; FOOD; ADULTERATION; GRAIN; Chemistry; Food Science & Technology; Nutrition & Dietetics